Pemeriksaaan Gula Darah untuk Mencegah Diabetes Melitus di Desa Bajo Indah, Kecamatan Soropia, Kabupaten Konawe, Sulawesi Tenggara - Rahman Rahman (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
Diabetes mellitus (DM) is increasingly prevalent globally, including in remote areas such as Bajo Indah Village in the Soropia District of Konawe Regency, Southeast Sulawesi. This community service project aims to monitor blood sugar levels to prevent the onset of diabetes mellitus and facilitate early detection in the region. Obtaining licenses, collaborating with local officials, and preparing medical supplies constituted the employed techniques. The implementation stage involved outreach, interactive counseling, and blood sugar testing with a portable glucometer. Seventy-five individuals participated in the event on July 7, 2025. The findings indicated that 55 individuals (73.3%) exhibited normal blood sugar levels (≤ 140 mg/dL), while 20 individuals (26.7%) presented elevated levels (140–199 mg/dL). The findings indicate that individuals with elevated or diminished blood sugar levels require increased attention. Continuous education and referrals to healthcare facilities for additional treatment can mitigate complications associated with diabetes mellitus.